2023
DOI: 10.3389/fnagi.2023.1185671
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and lifestyle modifications in the treatment of neurodegenerative diseases

Abstract: Neurodegenerative diseases have reached alarming numbers in the past decade. Unfortunately, clinical trials testing potential therapeutics have proven futile. In the absence of disease-modifying therapies, physical activity has emerged as the single most accessible lifestyle modification with the potential to fight off cognitive decline and neurodegeneration. In this review, we discuss findings from epidemiological, clinical, and molecular studies investigating the potential of lifestyle modifications in promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 150 publications
0
7
0
Order By: Relevance
“…With a thorough understanding of these factors, we can begin designing interventions targeted at enhancing cognitive performance to decrease the risk of fractures in the elderly. Such interventions could encompass cognitive training, nutritional adjustments, and lifestyle enhancements [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…With a thorough understanding of these factors, we can begin designing interventions targeted at enhancing cognitive performance to decrease the risk of fractures in the elderly. Such interventions could encompass cognitive training, nutritional adjustments, and lifestyle enhancements [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial carried out by Ngandu et al in an intervention involving multiple domains showed that older persons at risk of dementia experienced enhanced cognitive performance by adhering to a Mediterranean diet, engaging in physical exercise, and participating in cognitive training [246]. Moreover, Shannon and colleagues had positive results when investigating the feasibility, acceptability, and mechanism of action of a multidomain intervention that focuses on the Mediterranean diet and Physical Activity (PA) for reducing the risk of dementia in a high-risk population [247,248]. Hsieh et al highlighted in their randomized controlled trial that home-based exercise and nutrition therapies specifically designed for pre-frail or frail older people suffering for cognitive decline can effectively enhance their frailty score and physical performance [249].…”
Section: Case Studies and Community-based Programs Of Exercise And Nu...mentioning
confidence: 99%
“…It's important to note that while traditional therapies can help manage symptoms and improve quality of life, they do not offer a cure for neurodegenerative diseases. Research is ongoing to develop disease-modifying therapies and explore innovative approaches, such as stem cell therapies and gene therapies, to address the underlying causes of these diseases 58 .…”
Section: Neurodegenerative Diseases and Their Characteristicsmentioning
confidence: 99%